Muslim Science Thought from The Perspective of Abu Bakr Muhammad Zakariya ar-Razi - Unzilatun Nikmah; Mawaddatul Jannah (STAI Ma'had Aly Al-Hikam Malang, 2024)
Many prominent and renowned philosophers and scientists in their respective fields were born by the Islamic civilization. With his book Al-Hawi fi al-Ṭibb, al-Razi, one of the Islamic scholars, had a great influence in the world of science. Although he adhered to the theocentric and anthropocentric paradigms, he rejected the